A study on the Requirements to Support the Accurate Prediction of Engineering Change Propagation. Issue 2 (23rd May 2017) - Koh, Edwin C. Y.
ABSTRACT: This paper builds on previous work in the area of design representation to identify the types of modeling information required to support the accurate prediction of engineering change propagation during the design of complex engineering systems. It uses the Function–Behavior–Structure (FBS) framework as a basis to examine how engineering changes can occur and how they may subsequently propagate. It was revealed that the relationship between change requirements and product components, the functional dependencies between product components, the behavioral dependencies between product components, and the structural dependencies between product components are all essential modeling information that need to be considered to fully describe the propagation of engineering changes. The essential modeling information identified can serve as modeling requirements to support the development of change prediction methods. In this work, three example design methods were discussed to examine the feasibility of using the modeling requirements for method evaluation. It was concluded that the level of accuracy achievable depends on the design context and hence a direct comparison between methods developed for different design contexts may not be meaningful. This suggests that accuracy should not be used as the sole criterion to evaluate change prediction methods.